Health Ombudsmen in Polycentric Regulatory Fields: England, New Zealand, and Australia. Issue 4 (6th March 2016) - Healy, Judith; Walton, Merrilyn
Abstract : Health ombudsmen (health complaints commissioners), an unusual entity internationally, exist only in England, New Zealand, and the Australian states and territories. Established to respond to complaints from patients, the intention is to make health services and professionals more accountable to the public. Most cases are handled around the softer base of a regulatory pyramid, such as advice to complainants and requests to providers for an explanation and/or apology. Few cases escalate to investigations and prosecutions. Although the legal powers of some health ombudsmen to redress individual grievances have been strengthened, most lack the independent power to initiate an inquiry into systemic problems. To produce quality improvements, health ombudsmen need powers to require compliance from providers and to initiate inquiries. With the advent of new health sector regulators, health ombudsmen must negotiate their role and function within expanding networks of governance. Abstract : Health ombudsmen warrant attention as unusual entities both internationally and given their statutory mandate to respond directly to patient complaints about health professionals and health services. They also act as a 'public watchdog' in making health institutions more accountable for making systemic improvements to their services.